Model kinetic and techno-analysis of moringa leaves hot air-drying process for sustainability development [pdf] - Ngô Văn Tài; Nguyễn Minh Thủy; Huynh Thi Thu Huong; Pham Cam Dang; Võ Quang Minh (Acta Scientiarum Polonorum Technologia Alimentaria, 2024)
Moringa oleifera is the most common species of woody plant in the genus Moringa in the family Moringaceae.This plant is native to South Asia but also grows wild and is grown, exploited, and used in many places in tropical and subtropical countries due to its high economic value.In countries where this plant is found, Moringa oleifera is used as a vegetable and in processed foods because of its nutritional properties.The leaves are high in protein, rich in flavonoids, carotenoids, and ascorbic acid, and contain essential amino acids (Anwar
Keywords: Moringa oleifera research and applications